Longitudinal study of five seasons of upper limb injuries in training and matches in elite female rugby union at club and national team level - White, C. S.; Garner, P.; Stokes, K. A.; Williams, S.; Horsley, I.; Kemp, S. P. T.; Sound, A. (BMJ Open Sport & Exercise Medicine, 2025)
Background Data on upper limb injuries in elite female rugby athletes are limited. This study aims to describe the incidence, severity and burden of upper limb injuries over five seasons in elite women`s rugby at both the club and international levels in training and matches.